Applicability of the low-density lipoprotein cholesterol gene score in a south European population - Mariano, C. (2017)
Aim: The correct identification of the dyslipidaemia is of great importance in order to implement specific interventions, especially for cardiovascular disease (CVD) prevention. The Global Lipids Genetics Consortium (GLGC) reported 158 loci associated with lipid traits, by genome-wide association studies (GWAS), although practical value of GWAS approach is still a subject of debate, half of these loci are previously known to influence serum lipid concentrations. Previous studies (Talmud et al., 2013; Futema et al., 2015) have demonstrated that the co-inheritance of low-density lipoprotein (LDLC)-raising alleles from 6 of these SNPs is associated with the Familial Hypercholesterolaemia (FH) phenotype. Here we investigated the applicability of the LDL-C genetic risk score in the Portuguese FH population.